ИССЛЕДОВАНИЕ ФЕРРОРЕЗОНАНСНЫХ ПРОЦЕССОВ БЕЗ ЗАМЫКАНИЙ НА ЗЕМЛЮ - Саенко, Ю.Л.; Попов, А.С. (Інститут електродинаміки НАН України, Київ, 2012)
Investigated ferroresonance processes that evolve without ground fault. Considered the principles of excitation of these processes. Shows the influence of load secondary winding voltage transformer on the flow processes ferroresonance. Show some results of calculations. References 13, tables 2, figures 5.